Análise das mudanças de processos e dos benefícios gerados com a implementação do RECOF automotivo - Bortolli, Luiz Olivio (2007)
With the globalization phenomenon, it opened very promising exportation market for the Brazilian industries, especially in the automotive segment. To be really competitive, beyond the low cost of the manpower, it is very important that it has the possibility to reduce the costs of raw material and components. With the fall of customs barriers, that leads companies to the intensification of foreign commerce and demands greater reduction of bureaucracy in the customs processes, aiming at the reduction of logistics costs and tributes. Brazil hosts currently, the main worldwide groups of the automotive segment, which develops the exports in this market. A recent study of the World Bank demonstrates that while the Brazilian products take, in average, 39 days to get permits, whereas in the remaining of the world, this process is around 27 days. To solve this problem, customs regimen RECOF appeared in 1997 for the Information Systems and Telecommunications business, and in 2002 for the automotive and aeronautical business. The objective of the present survey is to analyze the process changes and benefits generated by the automotive RECOF implementation. This survey is regarded as an applied and exploratory, inasmuch the methodological procedure was a case study. The main advantages achieved by this regimen are represented by the reduction of the logistics costs and the return of the capital used in the payment of the incident taxes to purchase raw materials and components.